If you made a million - Schwartz, David M.; Kellogg, Steven (New York : Lothrop, 1989)
Describes the various forms which money can take, including coins, paper money, and personal checks, and how it can be used to make purchases, pay off loans, or build interest in the bank.
Wilson's Children
Elem. School Library Collection
Notable/Best Books (A.L.A.)
3.9
K-3
Keywords: Finance, Personal -- Juvenile literature; Finance, Personal; Money; Finance, Personal; Money